2021
DOI: 10.1007/s00330-021-08409-4
|View full text |Cite
|
Sign up to set email alerts
|

Commercial AI solutions in detecting COVID-19 pneumonia in chest CT: not yet ready for clinical implementation?

Abstract: Objectives In response to the COVID-19 pandemic, many researchers have developed artificial intelligence (AI) tools to differentiate COVID-19 pneumonia from other conditions in chest CT. However, in many cases, performance has not been clinically validated. The aim of this study was to evaluate the performance of commercial AI solutions in differentiating COVID-19 pneumonia from other lung conditions. Methods Four commercial AI solutions were evaluated on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…Future implications of using computer tools might be implemented with fully automatic AI-based quantification software, such as Li L 2020 et al [ 33 ] and Jungmann F. et al [ 34 ] suggested in their study. This last one calculated the sensitivity, specificity, positive predictive value (PPV), the negative predictive value (NPV), and the area under the curve (AUC) for four AI solutions from different vendors compared to the visual score obtained by two radiologists to differentiate Sars-CoV-2 related pneumonia from other lung conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Future implications of using computer tools might be implemented with fully automatic AI-based quantification software, such as Li L 2020 et al [ 33 ] and Jungmann F. et al [ 34 ] suggested in their study. This last one calculated the sensitivity, specificity, positive predictive value (PPV), the negative predictive value (NPV), and the area under the curve (AUC) for four AI solutions from different vendors compared to the visual score obtained by two radiologists to differentiate Sars-CoV-2 related pneumonia from other lung conditions.…”
Section: Discussionmentioning
confidence: 99%
“…A clinical example of this model can be found in other studies, such as Suri J.S et al [21] and Gujot J. et al [22], in which the earlier cited software offered a valid tool to detect and classify affected patients. Nevertheless, Jungmann F. et al [23] stated their concern regarding the actual AI solutions, such as Icolung, as tools to assess positive predictive value (PPV). The aim of this study was to evaluate the performance of commercial AI solutions in differentiating COVID-19 pneumonia from other lung conditions.…”
Section: Discussionmentioning
confidence: 99%
“…[165] Specific examples include development of automated tools for interpreting CT scans, chest X-rays and lung ultrasound diagnostics, [166][167][168][169][170] though clinical trials to establish the benefits and safety of image analysis in clinical practice are awaited. [171]…”
Section: Digital Innovation To Manage Covid-19 Infectionsmentioning
confidence: 99%